Fingerprint enhancement and compression method using Morlet wavelet. (11th January 2011) - Viswanathan, P.; Venkata Krishna, P.
Fingerprint image being a non-stationary image, the normal filtering approach and transformation like FFT will not provide efficient enhancement. This problem is studied using our new algorithm based on Morlet wavelet. This algorithm consists of two stages. In the first stage, wavelet analysis is used, which estimates contextual information like frequency and orientation of the image. The second stage uses Gabor filtering for smoothening and removing the noise. Good ridge continuity is obtained with compression and Gabor filtering removes the spurious minutiae. The experimental results obtained by this new algorithm provided accurate recognition and less storage compared with the existing approaches.